2011
DOI: 10.1063/1.3556986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythrocytes oscillations on dielectric properties of human diabetic-blood

Abstract: It has been demonstrated that the erythrocytes (RBCs) oscillate during their tank-treading motion with high-frequency oscillations. This oscillatory motion drastically affects the dielectric and electrical properties of RBCs. Moreover, the glucose level in blood affects the electrical and dielectric properties of blood. It has been, also, shown that the frequency of these oscillations exponentially decrease from 1.2 MHz down to 0.85 MHz with variation of glucose level from 85 mg/dL up to 346.1 mg/dL. It is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Radiation from a cell phone (850 MHz, 2 W uniform electromagnetic field) either significantly decrease or increase the blood cell counts in both normal and high glucose blood samples and is a function of the power level and testing duration. The effects previously has been attributed to many factors, including i) false signal from oscillating ions that affect the electrochemical balance of the plasma membrane and cell function [10], ii) the cell membrane effect [11], iii) the dielectric and electrical properties of the blood [29,30]. Discrepancies could also be due to the blood type, since blood samples used in each test come from different individuals, where the reaction mechanism is different, resulting in different response to the exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation from a cell phone (850 MHz, 2 W uniform electromagnetic field) either significantly decrease or increase the blood cell counts in both normal and high glucose blood samples and is a function of the power level and testing duration. The effects previously has been attributed to many factors, including i) false signal from oscillating ions that affect the electrochemical balance of the plasma membrane and cell function [10], ii) the cell membrane effect [11], iii) the dielectric and electrical properties of the blood [29,30]. Discrepancies could also be due to the blood type, since blood samples used in each test come from different individuals, where the reaction mechanism is different, resulting in different response to the exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Havas and Stetzer have shown that in an environment without electromagnetic fields, type I diabetes required less insulin, and type II diabetes have lower levels of plasma glucose [24][25][26], while research with electromagnetic pulses show a decrease in the glucose levels of type I diabetes in treated mice, primarily due to a decreased binding affinity between insulin and its receptor [27,28]. It has also been shown that electromagnetic radiation influences the glucose concentration, dielectric and electrical properties of the blood [29,30]. Electric field effect on insulin chain-B under static and oscillating conditions showed that the electric field caused a destabilizing effect on the peptide [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocytes oscillate with high-frequency oscillations during the tank-treading motion. This oscillatory motion drastically affects the dielectric and electrical properties of erythrocytes and the blood [19]. Experimental and the theoretical analysis indicate the absence of resonance frequencies in the range of 0.03-500Hz associated with the oscillations of normal human erythrocytes [20].…”
Section: Resultsmentioning
confidence: 99%
“…The rotation frequency (f0) could be calculated with the absolute value of the phase difference and the particle's induced dipole moment, together with the viscosity frictional forces. In the different references there is a common intrinsic ultrasound frequency of erythrocytes, f0∼ 1.2MHz [19].…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical and experimental dielectric studies were developed to explain the interactions between cells under normal and pathological conditions 811. An experimental approach using impedance spectroscopy was developed for the investigation of erythrocyte aggregation 12.…”
Section: Introductionmentioning
confidence: 99%